Protein Translation and Signaling in Human Eosinophils - Esnault, Stephane; Shen, Zhong-Jian; Malter, James S. (Frontiers in Medicine, 2017)
We have recently reported that unlike IL-5 and GM-CSF, IL-3 induces increased translation of a subset of mRNAs. In addition, we have demonstrated that Pin1 controls the activity of mRNA binding proteins, leading to enhanced mRNA stability, GM-CSF protein production and prolonged EOS survival. In this review, discussion will include an overview of cap-dependent protein translation and its regulation by intracellular signaling pathways. We will address the more general process of mRNA post-transcriptional regulation, especially regarding mRNA binding proteins, which are critical effectors of protein translation. Furthermore, we will focus on 1) the roles of IL-3-driven sustained signaling on enhanced protein translation in EOS, 2) the mechanisms regulating mRNA binding proteins activity in EOS, and 3) the potential targeting of IL-3 signaling and the signaling leading to mRNA binding activity changes to identify therapeutic targets to treat EOS-associated diseases.